(4x^2)^3*(3x^2)^2*(12x)^3*x^5=2736
_________________________
(4x^2)^3=(2^2*x^2)^3=2^6*x^6
(3x^2)^2=3^2*x^4
(12x)^3=(2^2*3*x)^3=2^6*3^3*x^3
2736=2^4*3^2*19
____________________________
2^6*x^6 * 3^2*x^4 * 2^6*3^3*x^3 * x^5 = 2^12 * 3^5 * x^18
2^12 * 3^5 * x^18 = 2^4*3^2*19
2^8 * 3^3 * x^18 = 19
x^18 = 19 / (2^8 * 3^3)
![x= +-\sqrt[18]{ \frac{19}{2^8*3^3} } =+- \frac{ \sqrt[18]{19} }{ \sqrt[9]{16} \sqrt[6]{3} } x= +-\sqrt[18]{ \frac{19}{2^8*3^3} } =+- \frac{ \sqrt[18]{19} }{ \sqrt[9]{16} \sqrt[6]{3} }](https://tex.z-dn.net/?f=x%3D+%2B-%5Csqrt%5B18%5D%7B+%5Cfrac%7B19%7D%7B2%5E8%2A3%5E3%7D+%7D+%3D%2B-+%5Cfrac%7B+%5Csqrt%5B18%5D%7B19%7D+%7D%7B+%5Csqrt%5B9%5D%7B16%7D+%5Csqrt%5B6%5D%7B3%7D++%7D+)
- действительные корни